PEREMPUAN SEBAGAI KOMODITAS WARUNG KOPI CETOL DI DESA GONDANGLEGI - 'arisi, Roffa el; Wati, Elya Kurnia; Meiji, Nanda Harda Prama (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The coffee shop is a second home for modern citizens amid the rise of coffee culture in male society. One way to attract customers with the existence by using women as waiters and even accompanying customers as in a small coffee shop. This study aims to find out: (1) how is the relationship between female waiters and customers in coffee shops, (2) the reasons why women are willing to work as waiters in cetol coffee shops, and (3) the views of the surrounding community on the existence of cetol coffee shops. The method used in this research is descriptive qualitative. The results obtained from this study indicate that the interaction pattern between the waiter and the cetol coffee shop customer uses symbols in providing services to customers, such as wearing tight clothes, sounding spoiled, and others. They work as servants because of economic factors, lack of job opportunities, and also want to fulfill their own needs independently, so these female servants do not care about the negative public response to their work.